Fabrication of Polyethersulfone-Based Symmetric Membrane by Applying Pause Stage in Coagulation - Mohammad Vahedi; Jalal Barzin; Mojegan Kowsari (علوم و تکنولوژی پلیمر, 2015)
Phase inversion is a common method for preparation of polymeric membranes. It is noticeable that most of the membranes prepared by this method have an asymmetrical structure. In this type of membranes, separation of particles occurs only by top dense layer in a high operating pressure. On the other hand, the separation process using symmetric membranes containing surface pores occurs on the top surface and in the depth of the membrane at lower operating pressure. In this research, preparation of polyethersulfone-based membranes was performed through the phase inversion method by dimethylacetamide as a solvent and water as the nonsolvent. Changing the coagulation conditions by applying one pause stage in an environment with the precise control of temperature and humidity, along with using polyvinylpyrrolidone as a hydrophilic additive, were attempted in order to controlthe porosity and structural changes of the membrane. Scanning electron microscopy (SEM) images, bubble point test, porosity, and mean pore radius measurements were used to study the structure of the prepared membranes. The performance of the membranes was evaluated by pure water permeation test and elimination of bacteria from cell culture medium. The results obtained illustrate that the implemented method is capable of preparation of membranes with symmetrical structure and pore diameter less than 0.4 μm featuring acceptable pure water flux and bacteria removalability. It was also observed that increase in the concentration of polyvinylpyrrolidone additiveleads to an increase in porosity, permeation and pore size of the membrane samples. On the other hand, the tensile strength and elongation-at-break of the membrane samples were reduced upon increasing in polyvinylpyrrolidone concentration.